Advanced microscopic characterisation of multi-scale high-resolution mechanical behaviour of a nacre-inspired composite. (November 2022) - Mo, Jingyi; Leung, Nathanael; Jargalsaikhan, Urangua; Wan, Hongbo; Zhu, Bin; Su, Bo; Sui, Tan
Abstract: A nacre-inspired composite with a lamellar architecture of polymethyl methacrylate (soft and tough phase) and alumina (stiff phase) was fabricated using a bidirectional freezing casting technique. The bulk fracture mechanics of the nacre-inspired composite has been reported along with detailed microstructural analysis. The mechanistic connection between microstructure and mechanical properties at the micro- and macro-scale was not fully understood. Herein we addressed this issue by quantifying phase-specific hardness, modulus, and residual stress at the micro-scale level and compared with the bulk mechanical response. A shear-lag model was applied to provide a quantitative understanding of the softening effects resulting from residual stress and the microstructure. Our findings demonstrated the potential of bioinspired synthetic architectures in providing a tuneable model system to investigate the underlying design principles of more complex hierarchical biological materials. Graphical abstract: Image 1 Highlights: Phase-specific mechanical properties at the microscale were correlated with the bulk mechanical properties. The correlation between residual stress, microhardness, microstructure, and macro-scale modulus was established. Shear-lag model was applied to quantify softening effects led by residual stress and microstructure. Our work shows the potential of bioinspired composites to study the design principles of more complex natural materials.